2016
DOI: 10.1016/j.immuni.2016.01.024
|View full text |Cite
|
Sign up to set email alerts
|

MAP Kinase Inhibition Promotes T Cell and Anti-tumor Activity in Combination with PD-L1 Checkpoint Blockade

Abstract: Targeted inhibition of mitogen-activated protein kinase (MAPK) kinase (MEK) can induce regression of tumors bearing activating mutations in the Ras pathway but rarely leads to tumor eradication. Although combining MEK inhibition with T-cell-directed immunotherapy might lead to more durable efficacy, T cell responses are themselves at least partially dependent on MEK activity. We show here that MEK inhibition did profoundly block naive CD8(+) T cell priming in tumor-bearing mice, but actually increased the numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
439
2
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 620 publications
(497 citation statements)
references
References 56 publications
(67 reference statements)
35
439
2
4
Order By: Relevance
“…Although MAPK signaling is important for early steps of T cell activation, 64,65 several studies have shown that MEK inhibitors reprogram the tumor microenvironment and potentiate responses to checkpoint immunotherapy. 6668 In these studies, tumor growth was reduced by the combination of MEK inhibitors and various forms of immunotherapy, but tumors were not completely eradicated. It would be interesting to test whether RON and MEK inhibitors can cooperate to provide a better therapeutic outcome in the context of checkpoint immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Although MAPK signaling is important for early steps of T cell activation, 64,65 several studies have shown that MEK inhibitors reprogram the tumor microenvironment and potentiate responses to checkpoint immunotherapy. 6668 In these studies, tumor growth was reduced by the combination of MEK inhibitors and various forms of immunotherapy, but tumors were not completely eradicated. It would be interesting to test whether RON and MEK inhibitors can cooperate to provide a better therapeutic outcome in the context of checkpoint immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were mechanistically explained by another study using the same model. Ebert et al [112] demonstrated that MEK inhibition profoundly blocks naive CD8 T-cell priming. At the same time, this pharmacological inhibition increases the number of antigen-specific effector CD8 T cells in the tumor and protects CD8 TILs from death driven by chronic TCR stimulation [112].…”
Section: Mek Inhibitionmentioning
confidence: 99%
“…However, from serial tumor biopsy specimens of melanoma patients receiving BRAF and MEK inhibitors as well as from in vivo experiments with MEK inhibitors, it became clear that MEK inhibitors stimulate MITF and melanocyte-lineage antigen expression and augment T cell infiltration (18,24). Furthermore, MEK inhibitors have an additional antitumor immunity effect, by inhibiting the interaction between tumor cells and "M2-like" macrophages, which does not allow the entry of effector T-cells into the tumor (25,26). These effects make very appealing the combination of MEK inhibitors with ICB even for BRAF wild-type melanoma patients.…”
Section: Introductionmentioning
confidence: 99%